Study on the Stratigraphic Framework and Main Control Factors of Hydrocarbon Formation in Thin Reservoirs of Carboniferous Clastic Rocks in Tahe Oilfield - Deng Feng; Sun Li; He Youjuan; Hou Huaxing; Yang Zhi (E3S Web of Conferences, 2022)
The Carboniferous Karashayi Formation in Tahe Oilfield is one of the most promising formations in the field of clastic rocks in Tahe Oilfield, which is rich in hydrocarbon resources, but the stratigraphic framework is unclear, which restricts the exploration of hydrocarbon formation. The stratigraphic features and seismic section analysis of the area combined with oil and gas distribution are used to analyze the stratigraphic framework and reservoir control factors of the Karashayi Formation. The results show that the lower part of the Carboniferous sedimentary strata is overburdened and the top part is denuded. The Karashayi Formation can be divided into four tertiary sequences and seven system domains. The oil and gas reservoirs are mainly developed near the interface of the sequences. Good transport conditions and stratigraphic unconformity cusp blocking can also make the marine intrusion system domain a favorable location for oil and gas accumulation. The Carboniferous Karashayi Formation is located on a convex overburden background and is a composite reservoir controlled by a stratigraphic unconformity and stratigraphic sharp extinction, which is influenced by tectonics, fractures, and lithology.